2021
DOI: 10.1111/jfpe.13795
|View full text |Cite
|
Sign up to set email alerts
|

Process effectiveness assessment by modeling the kinetics of lotus seed drying combining air‐borne ultrasound and microwave vacuum

Abstract: This study presents the effects of ultrasound (US) on the drying kinetics of lotus seeds in a hybrid dryer equipped with constant microwave power in combination with airborne US at vacuum degree (USMVD) and atmospheric pressure (USMD) from 120 to 440 W of five US power levels. Water‐borne US pretreatment before microwave drying (US + MD) or microwave vacuum drying (US + MVD) was simultaneously performed to compare their effectiveness in drying lotus seeds under the same US power. USMD and USMVD techniques redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In the study of Xu et al (2022), the USMD process reduced the drying time of T. fuciformis by up to 42.86% compared to the ultrasonic pretreatment-assisted microwave drying method, and effective moisture diffusivity increased from 1.72 × 10 −5 to 2.28 × 10 −5 m 2 /s. When the microwave power is constant, the increase of ultrasonic power can improve drying efficiency (Wang, Lei, et al, 2021). It is due to the facilitated drying by reduced mass transfer resistance in the food materials on both surfaces and their internal regions, with the increased ultrasonic power (Kowalski et al, 2016).…”
Section: Drying Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…In the study of Xu et al (2022), the USMD process reduced the drying time of T. fuciformis by up to 42.86% compared to the ultrasonic pretreatment-assisted microwave drying method, and effective moisture diffusivity increased from 1.72 × 10 −5 to 2.28 × 10 −5 m 2 /s. When the microwave power is constant, the increase of ultrasonic power can improve drying efficiency (Wang, Lei, et al, 2021). It is due to the facilitated drying by reduced mass transfer resistance in the food materials on both surfaces and their internal regions, with the increased ultrasonic power (Kowalski et al, 2016).…”
Section: Drying Efficiencymentioning
confidence: 99%
“…The reduction in drying time by USMD inhibits the degradation and oxidation of these nutrients. Lei et al (2021) reported that the USMD method significantly reduced the loss of total sugar, total phenols, and total antioxidants in dried mushrooms. Similarly, Xu et al (2022) reported that the USMD samples showed maximum protein and total sugar content.…”
Section: Nutritional Componentsmentioning
confidence: 99%
See 1 more Smart Citation